2020
DOI: 10.1186/s12912-020-00496-w
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ethical leadership on subjective wellbeing, given the moderator job satisfaction (a case study of private hospitals in Mashhad)

Abstract: Background The emerging ethical leadership, a unique approach in leadership viewpoint, has provided the ground for constructing and advancing individual and managerial efficiency by highlighting ethics in organizations. The present study aims to investigate the influence of Ethical Leadership on Subjective Wellbeing, Given the Moderator Job Satisfaction in Private Hospitals in Mashhad. Methods This descriptive-correlational research design stud was conducted in 2015–2016 to inspect the possible effect of ethi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 32 publications
3
15
0
Order By: Relevance
“…The specialized literature on job satisfaction reveals that it is an integral part of any industry or work environment. In the case of health workers, it was found that ethical leadership positively and significantly influences job satisfaction, by: applying ethical principles to problem-solving and equity [ 24 ]; offering training and organizational support [ 25 ] together with management support and resources, despite tendencies to quit the job [ 26 ]; offering psychological support despite difficult working conditions [ 27 ]; prompting risk prevention plans [ 28 ]; offering improved health maintenance programs [ 29 ]. In all the previously mentioned sources, well-being was either positively or negatively affected by management decisions.…”
Section: Introductionmentioning
confidence: 99%
“…The specialized literature on job satisfaction reveals that it is an integral part of any industry or work environment. In the case of health workers, it was found that ethical leadership positively and significantly influences job satisfaction, by: applying ethical principles to problem-solving and equity [ 24 ]; offering training and organizational support [ 25 ] together with management support and resources, despite tendencies to quit the job [ 26 ]; offering psychological support despite difficult working conditions [ 27 ]; prompting risk prevention plans [ 28 ]; offering improved health maintenance programs [ 29 ]. In all the previously mentioned sources, well-being was either positively or negatively affected by management decisions.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of ethical leadership relates well to positive employee psychology literature. A positive link between ethical leadership and employees' subjective wellbeing has been repeatedly discussed in prior literature (Yang, 2014 ; Kaffashpoor and Sadeghian, 2020 ). Specifically, the literature argues that an ethical leader enhances employees' mental health by focusing on their issues and facilitating them in achieving different organizational tasks (Li et al, 2014 ).…”
Section: Theory and Hypothesesmentioning
confidence: 70%
“…However, as far as we know, no research has yet analyzed its moderating role between telework and wellbeing. Some support for this mediating role can be based on recent research, which confirms that job satisfaction mediates the relationship between various job conditions and wellbeing [50].…”
Section: Telework Job Satisfaction and Wellbeingmentioning
confidence: 93%
“…These evaluations reflect both objective living conditions as well as psychological wellbeing [49]. Thus, a subjective approach is used to determine quality of life, which includes areas such as physical, psychological, and spiritual wellbeing [50].…”
Section: Telework Job Satisfaction and Wellbeingmentioning
confidence: 99%